On the Biblical and indigenous Characteristics of Lian Jianzhong’s Literary Writings - LIU, Lixia (Journal of Research for Christianity in China (JRCC), 2022)
In the 1940s, the development of Chinese Christian literature showed a more obvious characteristic of indigenization. A representative as Lian Jianzhong (Lian Ronghu),a poet from Wuxi, published a series of Chinese Christian poems "A Hundred Hymns for Heavenly Logos", "Collections for Religious Poems", "A New Aria for Gospel" and other works on Collections for Christianity（《基督教丛刊》, Jidujiao Congkan）, and all in the form of Chinese traditional poetry. As a result, all these poems with Christian thought elucidated the Chinese traditional culture successfully and Its hard work was recommended and affirmed by the Christian scholar Wang Zhixin. In the process of indigenization of Chinese Christian literature, the integration made between Buddhism and Chinese literature can be used for reference for Christianity, which is the consensus reached by many Christian scholars, such as Wang Zhixin, Zhao Zichen and Liu Nairen.